The Contribution of Learning Culture and Soft Skills in Improving the Character of High School Students - Wardhani, Ni Ketut Sri Kusuma; Mahendradhani, Gusti Ayu Agung Riesa (Mimbar Ilmu, 2024)
Character is a key issue in education, highlighted by the rise of adolescent promiscuity, drug abuse, crime, and radicalism, indicating a deepening moral crisis. This study aims to analyze the influence of learning culture and soft skills in improving the character of high school students. This type of research is survey research. The approach to this research is quantitative, with an ex post facto research design. The population of the study was 361 students. The sample was taken using the proportional random sampling technique with random sampling. The number of samples in this study was 218 people. Data were collected using the questionnaire method and document recording. Meanwhile, the instrument used to collect data was a questionnaire sheet. Data were analyzed using descriptive and inferential statistical analysis techniques. The results of the study showed a very significant path coefficient. Analysis of learning culture on student character obtained a very significant path coefficient, proving that learning culture has a direct positive effect on student character. Analysis of learning culture on student characteristics through soft skills obtained an indirect effect. Learning culture has a significant effect on student soft skills with a contribution of 65.5%. Learning culture and soft skills have a direct effect on student character with a contribution of 66.8%. It is concluded that, student character can be formed through a good learning culture and soft skills.